Poland-Mobius syndrome in an infant girl - Al-Mazrou, Khalid A. (Medknow Publications, 2009)
Mobius syndrome is a rare condition of unclear origin, characterized by a unilateral or bilateral congenital facial weakness with impairment of ocular abduction, which is frequently associated with limb anomalies. Poland described a condition in which there was unilateral absence of pectoralis major muscle and ipsilateral syndactyly. The combination of Poland-Mobius syndrome is rare, with an estimated prevalence 1:500 000. We describe a case of Poland-Mobius syndrome in association with congenital bilateral vocal fold immobility. To our knowldge, this is the first report of such an association between Poland-Mobius syndrome and congenital bilateral vocal fold immobility.